Accommodative convergence–accommodation ratio and fusional capacity in patients with constant and intermittent exotropia (Ukrainian Journal of Ophthalmology, 2025)
Background: It has been reported that exotropia was seen in 16.9-23% of patients with strabismus. Exophoria and exotropia may be caused by congenital or acquired anomalies in orbital structure, ocular structure, or extraocular muscle attachment and/or location. Planning conservative treatment or time and amount of surgery for patients with exotropia will require advances in diagnostic techniques for the ocular motor and sensory system.Purpose: To determine the features of the state of accommodation and state of fusion in patients with constant and intermittent exotropia.Material and Methods: Fifty nine patients with exotropia (age, 10 to 21 years) were under surveillance. Of these, 33 (group 1) had constant exotropia and 26 (group 2), intermittent exotropia. The near point of convergence, the accommodative convergence–accommodation (AC/A) ratio and phoria and near and distance and fusion were assessed. Patients underwent a routine eye examination. In addition, the near point of convergence was determined by the proximeter, the AC/A ratio was measured by the heterophoria method, and fusional reserves were measured using the synoptophore method.Results: High AC/A ratios were more common in constant exotropia than in intermittent exotropia (53.5% versus 38%, respectively), likely due to a low accommodative convergence. The AC/A ratio was found to be statistically significantly correlated with the angle of deviation at distance in group 1 (r=0.71), angle of deviation at distance in group 2 (r=0.65), and angle of deviation at near in group 1 (r=-0.61) (p < 0.05). The interaction of accommodation and convergence was impaired since the AC/A ratio in both groups was greater than a norm value of 3-5 diopters per prism diopter. This should be taken into consideration when prescribing optical correction and orthoptic treatment for exotropia.
Keywords: exotropia; accommodation; fusion; AC/A ratio